Extracutaneous neutrophilic infiltration of the spleen and lung associated with pyoderma gangrenosum of the skin. (5th January 2022) - Arai, Sakurako; Furukawa, Nao; Takahama, Makoto; Kodai, Shintaro; Ishii, Naomi; Nakagawa, Hidenori; Yamasaki, Tomoaki; Kusutani, Nao; Maekawa, Naoki; Fukai, Kazuyoshi
Abstract : We describe a patient with extracutaneous pyoderma gangrenosum (PG), who presented with chest pain. Histological examination showed extracutaneous neutrophilic infiltration of the spleen and lung, with later findings of PG.